Student written comments about stylistics in an ESL literature classroom - Mohd Nasir, Nora (IIUM Press, 2013)
This principle objective of this paper is to examine the implications of using stylistics in the teaching of literature. Contrary to traditional approaches, stylistics avoids significant subject bias by studying texts from a linguistic perspective. It aims to improve students’ ability to grasp complex works by equipping them with the tools with which to parse out meaning instead of relying solely on intuition and vague creative inclinations. This would increase the accessibility of literature by reducing the subjectivity of analysis and encouraging a more methodical style of investigation. This study was conducted using a qualitative research approach known as introspection. Data was collected in a class of 40 students through written responses to an open-ended question regarding their individual experiences learning stylistics. The findings of this study show that students benefit from stylistics with regards to honing their analytical prowess as well as heightening their comprehension of literary texts. In addition, this study could show that stylistics can indeed provide students with the necessary skills to achieve a more thorough and effective interpretation and understanding of literature.